G97 RANGE OF URINARY STEROID METABOLITE RATIOS IN CHILDREN UNDERGOING INVESTIGATION FOR SUSPECTED DISORDERS OF STEROID SYNTHESIS. (4th June 2013) - Lucas-Herald, A; Rodie, M; Liu, N; Rankin, K; Watson, N; Donaldson, M; Shaikh, MG; McNeilly, J; Shapiro, D; Ahmed, SF
Abstract : Background: Calculation of a urinary steroid metabolite ratio (uSMR) may be a useful method of improving diagnostic yield when investigating disorders of steroid hormone synthesis. Objective and hypothesis: To investigate the range of uSMR in children with suspected disorders of steroid hormone synthesis. Population/Methods: Ten ratios were calculated on steroid metabolite data analysed by GC-MS in urine samples collected between 2008–2010 from 219 children who were undergoing investigations. To obtain reference data, urine samples were also analysed in 89 children with no background of endocrine concerns and who had a urine sample collected at presentation to the hospital with an acute illness. Results: Of the 89 reference children, 36(40%) were male and median age at time of the test was 3 yrs(range, 1month-11yrs). Of the 219 endocrine patients, 64(29%) were boys. In 129(59%) cases, a urine sample was collected to investigate early or exaggerated signs of adrenarche. Median age at test was 7.4yrs(1day-18yrs). Median and ranges of 2 steroid ratios used in the diagnosis of 21-hydroxylase deficiency are demonstrated in the Table. Abbreviations: 17HP: 17-hydroxypregnanolone, PT: pregnanetriolone, THE: tetrahydrocortisone, THF: tetrahydrocortisol. Conclusions: These novel data show that reference ranges for urinary steroid metabolite data need to be age matched. Most children with suspected disorders of steroid synthesis have a ratio which is within the reference range and the identification of outliers will lead to better targeting of genetic analyses.